Analisis Pengaruh Diskon Terhadap Daya Beli Masyarakat Di Era New Normal (Studi Kasus Pengguna Shopee Di Kabupaten Sidoarjo) - Cahyono, Aralda Febrian; indrarini, rachma (Universitas Negeri Surabaya, 2021)
There is a purpose of this study to determine the effect of discounts on people's purchasing power in Sidoarjo district in the new normal era. This research uses quantitative methods and analytical tools using validity and reliability methods as test instruments, simple linear regression method, hypothesis method (T), and coefficient of determination method (R2). The results of this study indicate that the discount variable has a positive and significant effect on the variable of people's purchasing power in Sidoarjo district. The application of discounts in the new normal era can increase the purchasing power of people in Sidoarjo district.